Academic Freedom in US Higher Education: Rights Emergent from the Law and the Profession - Jeffrey C. Sun (Encyclopedia, 2025)
The various definitions of academic freedom in the United States reflect the influence of social and political norms in its interpretation as both a professional and legal right. Yet, underlying these interpretations is the operational understanding, which includes both legal and professional considerations, that academic freedom is a widely recognized principle that grants professors the autonomy and authority to explore intellectual questions within their academic disciplines, conduct professional work, and express their views in the public sphere without undue interference or suppression. In other words, academic freedom is a foundational principle rooted in legal and institutional frameworks that safeguards professors’ ability to engage in intellectual inquiry, professional practice, and public discourse without undue interference. This principle extends beyond mere professional courtesy. It is recognized as essential to the functioning of higher education institutions and the broader democratic exchange of ideas. The public (including policymakers, industry leaders, media, and students) generally acknowledges academic freedom as an inherent protection that protects from unjustified interferences. By doing so, professors can participate in governance, disciplinary leadership, and extramural activities without the fear of retaliation or coercion. By insulating academic work from ideological, political, or economic constraints, academic freedom maintains the legitimacy and independence of scholarly inquiry in service to both knowledge advancement and the public good.